Slavery, racial inequality, and education - Graziella Bertocchi (IZA World of Labor, 2015)
Income inequality is a critical issue in both political and public debate. Educational attainment is a key causal factor of continuing inequality, since it influences human capital accumulation and, as a consequence, the unequal distribution of earnings. Educational inequality displays a racial dimension that is particularly persistent and difficult to eradicate through policy measures. Its roots lie in the colonial institution of slave labor, which was widespread in the US and Latin America up until the 19th century. However, the influence of slavery differs significantly across countries and between regions.
Keywords: J15; O15; I24; 330; slavery; education; racial inequality